Food intake rhythm and its implication on obesity, and related comorbidities among adolescents: a mini review. Issue 6 (2nd November 2018) - Dutta, Koumi; Sen, Devashish; Sahu, Subhashis
Abstract: Purpose of the review: Food quality and quantity has always been explored to comprehend obesity and related comorbidities. The temporal component of food intake and the manifestation of circadian misalignment on it is an area to delve into.Recent Findings: Adolescence is a pivotal phase of life span, where an escalation in eveningness inclination has been observed. In developing countries like India, with the advent of globalization: sleep, activity, dietary pattern has undergone drastic changes. The cumulative effect of erratic feeding pattern and declination of physical activity has culminated into various comorbidities. Indian scenario of incidence of cardiovascular diseases, diabetes mellitus type II and other respiratory disorders are a booming cause of concern. Identification of the cogent relationship between food intake pattern and circadian typology among Indian adolescents are necessary to delineate chrono-obesity.Summary : Proper combination of sleep, activity and time restricted feeding is necessary to regulate diet-induced obesity. Arresting "Diabesity" with re-orientation of lifestyle and circadian realignment can be a primordial treatment or preventive step to decrease infestation of comorbidities among young adults.